Determinants of Gross Domestic Product in Asean Countries: Evidence from Panel Data Analysis (2002–2023) - Nico Sutjitro; Suyanto Suyanto (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study examines the effects of population size, unemployment rate, control of corruption, foreign direct investment (FDI), government effectiveness, and political stability on the Gross Domestic Product (GDP) of ten ASEAN member states during 2002–2023. Using a balanced panel dataset with 1,540 observations, the study applies Common Effect, Fixed Effect, and Random Effect panel regression models, with the Common Effect Model selected as the most appropriate estimator. The results show that population has a significant negative effect on GDP, indicating that demographic growth without corresponding productivity improvements may constrain economic output. In contrast, unemployment is positively associated with GDP, suggesting structural shifts toward capital- and technology-intensive production that weaken the link between output growth and labor absorption. Control of corruption and FDI both have significant positive effects, highlighting the importance of institutional quality and capital inflows in promoting economic growth. Government effectiveness exhibits a significant negative coefficient, which may reflect differences in economic scale among ASEAN countries. Political stability has a positive and significant impact on GDP, confirming its role in supporting sustainable economic development. Overall, the findings emphasize the importance of demographic, institutional, and investment-related factors in shaping economic performance across ASEAN economies.